Gold and Silver Catalysts for Liquid Phase n-Octanol Oxidation: Effect of Promoters; Current Organic Synthesis; Vol. 14, iss. 3 - Kotolevich Yu. I. Yuliya; Kolobova E. N. Ekaterina Nikolaevna; Pestryakov A. N. Aleksey Nikolaevich; Cabrera O. J. E. Ortega Jesus Efren; Bogdanchikova N. E. Nina Evgenjevna; Cortes C. V. Corberan; Khramov Evgeny E. A.; Zubavichus Ya. V. Yan Vitautasovich; Zanella Rodolfo R. A.; Pakrieva E. G. Ekaterina Germanovna (2017, 2017)
Title screen